STATISTICAL RESEARCH OF A STATE AND DEVELOPMENT OF INDICATORS OF INVESTMENT ACTIVITY IN THE MOSCOW REGION - Svetlana N. Zhuravleva (Статистика и экономика)
The study volume, structure and dynamics of investment companies Moscow region will be carried out using the methods ofeconomic-statistical, ﬁnancial and economic analysis, includingmethods of statistical observation methods grouping detail anddata visualization, tabular and graphical analysis methods,modeling and forecasting, coefﬁcient method, horizontal, vertical and trend analysis.As part of the study will be conducted state and dynamics ofinvestment activity on the territory of the Moscow region, in retrospect at least 5 years; medium-term forecasting indicators ofinvestment activity on the territory of the Moscow region.Study of volumes and dynamics of investment organizationsof Moscow region will conduct a comparative analysis of themain trends of changes in the state and dynamics of the ﬁxed assets of the Moscow region with the dynamics and structureof investment banking, to identify the main problems, disparitiesand particularly investment in ﬁxed assets in the Moscow region.